Longitudinal associations between mother–child conflict and child internalizing problems in mid-childhood. (14th February 2022) - Lougheed, Jessica P.; Duncan, Robert J.; Keskin, Gizem; Marceau, Kristine
Abstract: Several aspects of mother–child relationships are associated with children's internalizing problems. We examined longitudinal associations between mother–child conflict and children's internalizing problems in middle childhood. Specifically, we examined whether conflict and children's internalizing problems predict each other longitudinally in a sample of children from 3rd through 6th grade ( N = 1, 364) and their mothers using a cross-lagged panel model with random intercepts. In line with expectations, we found stable between-family differences in both mother–child conflict and children's internalizing problems. Contrary to expectations, we did not find that mother–child conflict and children's internalizing problems showed significant cross-lagged associations. However, mother–child conflict and children's internalizing problems had correlated errors at each wave, indicating that these two constructs covary with each other concurrently at multiple times across development, independent of stable between-family associations (i.e., as one increases, so does the other, and vice versa). The results of this study point to the importance of using statistical approaches that can disentangle between-family differences from within-family processes. In future studies, shorter time scales (e.g., weeks or months) may better capture dynamic associations between parent–child conflict and internalizing problems.